Training for Instructors Teaching Inclusive Postsecondary Education Program Students - Enoh Nkana; Robin Moyher; Luana Greulich; Larry Burton (Journal of Inclusive Postsecondary Education)
The passage of the Higher Education Opportunity Act in 2008 triggered an increase in inclusive postsecondary education (IPSE) programs across the United States, giving students with intellectual and developmental disabilities the opportunity to enroll in typical college courses. A multiple case study of IPSE programs at five institutions of higher education was conducted. Interviews of program directors and other program affiliates examined their roles in the development, components, and implementation of training programs, followed by observation of faculty development sessions and analysis of the documents used for training. Findings indicated no unified approach to faculty training, but similarities existed in the processes and resources used. Components included an introduction/overview of the program, inclusive instructional practices, and accommodations and modifications to course material.